Tourism for the elder, post-globalization, and transition: Mexico and the world, 2020–2050 (Terr@ Plural, 2022)
The main goal of this paper is to identify the new patterns that tourism will assume due to demographic changes to be experienced by the Mexican and other societies during the next three decades. Through a Qualitative Approach, the main source of information was obtained by comparative assessments of academic and periodical data enriched by the conduction of personal interviews with decision-makers involved in Tourism both in Mexico and in the United States. The document points out that the main factors that will undoubtedly change the tourist activity are, in addition to the process of population aging, the conditions of inequality generated by the globalization model, and the effects of the COVID -19 pandemic. The results suggest that tourism will face the challenge of reinventing itself, turning towards the local-regional and toward the elder segment of the population leaving behind the massive ingredients that tourism prioritized during the rise of the globalization model.
Keywords: Accessible Tourism; Globalization; Population Aging